Combined Immunosuppression Impairs Immunogenicity to Tetanus and Pertussis Vaccination Among Patients with Inflammatory Bowel Disease. Issue 8 (August 2015) - Dezfoli, Seper; Horton, Henry A.; Thepyasuwan, Nattapaun; Berel, Dror; Targan, Stephan R.; Vasiliauskas, Eric A.; Dubinsky, Marla; Shih, David Q.; Kaur, Manreet; McGovern, Dermot P. B.; Ippoliti, Andrew; Feldman, Edward J.; et al.
Abstract : Background: Pertussis epidemics have recently emerged across the United States, prompting broad public health recommendations for adult Tdap vaccination (tetanus, diphtheria, acellular pertussis). The impact of immunosuppressive regimens for inflammatory bowel disease (IBD) on vaccine responses to the Tdap vaccine is not known. Methods: We performed a prospective controlled trial between April 2011 and March 2012. Adults with IBD were consecutively stratified based on therapeutic regimen into one of 5 groups: A: no IBD therapy or 5-aminosalicylates alone; B: maintenance biologic monotherapy; C: maintenance immunomodulator monotherapy; D: combined biologic and immunomodulator therapy; and E: healthy age-matched controls. Subjects received Tdap, and serum antibody levels against tetanus toxoid, pertussis toxoid, and filamentous hemagglutinin (FHA) were drawn just before and approximately 4 weeks after vaccination. The primary outcome was the booster response rate to each antigen. Secondary outcomes included the differences in pregeometric and postgeometric mean titers. Results: A total of 98 subjects enrolled, and 84 completed the study. Tetanus response rates were 55%, 56%, 40%, 27%, and 63% across groups A to E, respectively. Group D rates were lower than those of group B ( P = 0.02). Postvaccination pertussis toxoid responses were 59%, 72%, 47%, 45%, and 75%, while FHA responses were 86%, 72%, 80%, 64%, and 75% across groups A to E, respectively. Prevaccination and postvaccination geometric mean titer differences for FHA were lower in group D than those in group A ( P = 0.05). Conclusions: Antibody responses to tetanus and pertussis vaccination may be affected by therapeutic drug regimen. Patients with IBD should optimally receive Tdap before starting immunomodulators, particularly when used in combination with anti–tumor necrosis factor alpha agents. Abstract : Article first published online 15 May 2015